PENGARUH PENJUALAN DAN HARGA POKOK PENJUALAN TERHADAP LABA BERSIH - Priyadi, Joko; Michael; Wardana, Aditya Wisnu (Perwira Journal of Economics & Business, 2022)
This study aims to determine, explain, and analyze the effect of Sales and Cost of Goods Sold on Net Profit in manufacturing companies in the basic and chemical industrial sectors of the wood and processing sub-sectors listed on the Indonesia Stock Exchange in 2018-2020. The number of samples taken is 4 (four) wood and processing sub-sector companies from 5 populations of wood and processing companies that have published complete annual financial reports during the study period. The sampling technique used is purposive sampling. The research method used in this study is a quantitative verification method. Based on the results of the research data analysis, the results obtained where; sales have a significant positive effect on net income. and Cost of Goods Sold in the partial test has a positive effect on net income, in the simultaneous or concurrent test, Sales and COGS are known to have a significant effect on net income.